Análisis y propuesta de un manual de seguridad y salud ocupacional Para El Talento Humano De La Empresa frio servicios del cantón lago agrio, provincia de Sucumbíos, para el año 2015 - Torres Armijos, Irene Rocío (2016)
The present research has as its main objective to propose a Manual Occupational Safety and Health for the Human Talent Cold Company Services Lago Agrio Canton, in order to provide a tool to provide with guidelines serve to prevent and control occupational hazards that exist in the company; and encourage compliance with the Standards of Occupational Safety and Health, to ensure the safety of workers and good working environment. In raising this tool, it follows that cover the problems that hinder the normal functioning and development of activities by workers, meeting the requirements or difficulties concerning Occupational Safety and health, such as lack of safety equipment, maintenance tools, lack of strategies for risk prevention, so that the company will comply with the provisions of the law, improving all processes. The study was based on the application of an inductive method, deductive, analytical descriptive with which it was possible to identify the causes of the risks, deduce the results, based on the information achieved with the application of techniques of field study, observation direct, interviewing the 16 employees of the company Frio Services (Manager, administrative staff, operational staff), so that allowed us to identify the requirements and needs of the company in terms of Occupational Safety and Health. instruments monitoring and evaluation (matrix) were also applied, for measuring the level of each of the risk factors and thus to make an estimate, to punctuate corrective and preventive measures to analyze the level of risk, will check the guidelines to follow, among the findings was determined under knowledge of safety regulations, lack of preventive measures, there is unsafe work environment. With the executed diagnosis follows that when the company does not have a manual for Occupational Safety and Health, where the procedures and processes of the company, providing workers with the comprehension and understanding of the rules and laws describing, so understanding of each of their activities, the manual also contains regarding rights and obligations, you will faithfully comply with the provisions of the manual.